High Risk of Cybercrime, Threat, Attack and Future Challenges in Nepal - Giri, Shailendra; Shakya, Subarna (International Journal of Computer Sciences and Engineering, 2020)
Government organizations, citizens, businesses are being victimized by cyber-attacks, crimes, and threats. Globally people have been using cyber safety in every sector of daily life but huge numbers of criminal activities are increasing day by day using ICT tools and applications. The purpose of this paper is to explorer the high risk of cyberattacks, crime, threat and future challenges in Nepal. The study was carried out using content analysis, analysis of various survey reports and in-depth interviews with subject experts. The study claims that high risk of a cyberattack, crime, and threat have been increasing unexpectedly in various sector of Nepalese society. It is essential to make a common strategy to reduce the increasing technical risk related to cyber. The risk of cyberattack, crime, and threat is very high. So, IT audit must be made compulsory in each and every organization and original operating system as well as application software used. Strong cybersecurity precautions and technologies ought to be adopted during the installation of ICT automation. The paper claims that not only the banking sector but also the Government of Nepal should appoint cybersecurity personnel in their services so that the expert team will be able to fight against the cyber attack. As time is demanding ‘Cyber Army’ in Nepal, the Government should not delay forming a new force ‘Cyber Army’.